Antidiabetic thiazolidinediones inhibit invasiveness of pancreatic cancer cells via PPARγ independent mechanisms. Issue 11 (11th October 2004) - Galli, A; Ceni, E; Crabb, D W; Mello, T; Salzano, R; Grappone, C; Milani, S; Surrenti, E; Surrenti, C; Casini, A
Abstract : Background/Aims: Thiazolidinediones (TZD) are a new class of oral antidiabetic drugs that have been shown to inhibit growth of some epithelial cancer cells. Although TZD were found to be ligands for peroxisome proliferators activated receptor γ (PPARγ) the mechanism by which TZD exert their anticancer effect is currently unclear. Furthermore, the effect of TZD on local motility and metastatic potential of cancer cells is unknown. The authors analysed the effects of two TZD, rosiglitazone and pioglitazone, on invasiveness of human pancreatic carcinoma cell lines in order to evaluate the potential therapeutic use of these drugs in pancreatic adenocarcinoma. Methods: Expression of PPARγ in human pancreatic adenocarcinomas and pancreatic carcinoma cell lines was measured by reverse transcription polymerase chain reaction and confirmed by western blot analysis. PPARγ activity was evaluated by transient reporter gene assay. Invasion assay was performed in modified Boyden chambers. Gelatinolytic and fibrinolytic activity were evaluated by gel zymography. Results: TZD inhibited pancreatic cancer cells' invasiveness, affecting gelatinolytic and fibrinolytic activity with a mechanism independent of PPARγ activation and involving MMP-2 and PAI-1 expression. Conclusion: TZD treatment in pancreatic cancer cells has potent inhibitory effects on growth and invasiveness suggesting that these drugs may have application for prevention and treatment of pancreatic cancer in humans.